2023
DOI: 10.3389/fgene.2022.1079455
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and mRNA expression of glutathione S-transferase alpha 4 are associated with intracranial aneurysms in a gender-dependent manner

Abstract: Objective: We performed a case-control study to investigate the correlation between DNA methylation and mRNA expression of the glutathione S-transferase alpha 4 (GSTA4) gene and the risk of intracranial aneurysm (IA) in the Chinese Han population.Methods: After propensity score matching, 44 pairs of cases and controls were collected in this study. Fasting blood samples were collected for DNA and RNA extraction within 24 h of admission. Nine CpG dinucleotides were selected from the GSTA4 promoter region for DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Still, these findings lacked replication and correction for multiple testing, casting uncertainty on their reliability. Additionally, a fourth study found lower DNAm levels and a higher mRNA expression of the glutathione S-transferase alpha 4 (GSTA4 ) gene involved in oxidative stress and phenotypic vascular smooth muscle cells (VSMC) transition, which is associated with IA risk, particularly in women [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Still, these findings lacked replication and correction for multiple testing, casting uncertainty on their reliability. Additionally, a fourth study found lower DNAm levels and a higher mRNA expression of the glutathione S-transferase alpha 4 (GSTA4 ) gene involved in oxidative stress and phenotypic vascular smooth muscle cells (VSMC) transition, which is associated with IA risk, particularly in women [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that IA patients exhibit lower levels of MAP3K10 methylation, which could potentially serve as a predictor of IA risk, particularly among women [ 24 ]. Additionally, DNA methylation and mRNA expression of glutathione S-transferase alpha 4 have been shown to be correlated with IAs in a gender-specific manner [ 25 ]. In addition, the DNA methylation of the patatin-like phospholipase domain-containing protein 6 gene has been implicated in contributing to the risk of intracranial aneurysms, especially in males [ 26 ].…”
Section: Introductionmentioning
confidence: 99%